OBTAINING ESTERS OF CITRIC ACID WITH HIGH ALIPHATIC ALCOHOLS (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
By esterification reaction of citric acid with pentadecylic, dodecylic, decyilic, and other alcohols the corresponding esters have been obtained. The effective novel methodologies of esterification reaction of citric acid at temperatures of 120–180°C with or without solvents are developed. The physical and chemical constants of the obtained compounds have been defined.
Keywords: citric acid esterification, pentadecylic, dodecylic alcohols